Palps across the tree – the neuronal innervation and development of sensory head appendages in Annelida - Kalke, Paul; Linder, Samira S.; Beckers, Patrick; Helm, Conrad (Frontiers in Neuroscience, 2024)
Polychaetes inhabit a wide variety of habitats and show a great morphological diversity. In this context, a key morphological structure for adapting to their individual lifestyles and ecological niches are the prominent head appendages. In the last years more and more studies focused on the mainly sensory annelid head appendages – namely the antennae, palps, buccal lips and cirri – to unravel the evolutionary origin and phylogeny of Annelida. Unfortunately, comparable data for most of the polychaete families are lacking so far, especially when it comes to features of the larval anterior nervous system and the related innervation and potential homology of these head appendages. In this study, we therefore use an integrative morphological approach including immunohistochemistry and confocal laser scanning microscopy in combination with histological serial sections and 3D-visualizations. With special focus on the palp-like appendages, our data provides a closer look into the development of the larval anterior nervous system and the related sensory structures of three polychaete families representing major groups of the annelid tree of life. Hence, we investigate members of the palaeoannelid Magelonidae as well as basally-branching Amphinomidae, and the pleistoannelid Spionidae forming a taxon deeply nested within Sedentaria. Our comparative data of larval and adult neuronal features support the homology of feeding-palps across the annelid tree. Furthermore, our observations show that larval palps gradually transform into the adult ones while keeping a very similar neuronal innervation pattern. Solely for Amphinomidae a loss of larval palps during ontogenesis has to be assumed. Therefore, our investigations uncover important and so far unknown details in terms of structural homology across Annelida and provide important results necessary for our understanding of annelid evolution.